Christian saints as described in the New Testament ... - Whately, Richard (Hodges and Smith [etc.], 1848)
The search after infallibility . -- Four sermons: (1) Fellowship in the gospel, (2) The Christianduty of educating the poor, (3) The search after infallibility, (4) Christian saints, as described in the New Testament. -- Mental culture required for Christian ministers. -- Essay on Christian self-denial. -- Address to the clergy and other members of the established Church, on the use and abuse of the present occasion for the exercise of beneficence. --